Why has Work Effort become more intense? Conjectures and Evidence about Effort-Biased Technical Change and other stories - Francis Green (University of Kent, Department of Economics, 2000)
I investigate possible explanations for work intensification, using four British data sets. I conjecture that an important source of work intensification is effort-biased technical change (EBTC), which enhances the productivity of high effort workers relative to that of low effort workers. EBTC can be traced to innovations such as Total Quality Management and to information technology, and is linked with multi-skilling. I argue that EBTC is complementary with skill-biased technological change. Additional sources of intensification are the increasing use of intra-firm communication policies, and the declining power of unions. All the above receive empirical support. However, evidence also shows that neither increased teamworking nor, contrary to popular expectations, changing job insecurity has raised average effort levels.
Keywords: J22; 330; Labour supply; work effort; work intensity; Arbeitsbedingungen; Technischer Fortschritt; Stress; Schätzung; Großbritannien